Оптимальное размещение рабочих мест с использованием математического аппарата φ-функций - Скорик, А. А. (ХНУРЭ, 2012)
The given work is devoted to the modern developments in the field of operations research and phi-functions theory. A new approach to the problems of technological objects‘ placing according to standards of labour and environmental protection was explored and described